Sul reificatore dimostrativo questo - Szantyka, Izabela Anna (Neophilologica, 2017)
The aim of the present paper is to define, describe and identify a phenomenon well-known in other scientific domains, but still a virgin soil in linguistics, and that is the reification, i.e. a linguistic tendency, intention and manifestation aimed to objectify and instrumentalize human referents by means of grammatical and lexical forms, traditionally employed to designate inanimate referents, such as demonstrative pronouns in their variable (in Italian) as well as neuter (in French) variants. In order to shed some light on this linguistic practice, we discuss the reifying uses of the Italian variable proximal pronoun questo, distinguished, analyzed and described on the basis of the linguistic material extracted from NUNC (NewsGroup UseNet Corpora) corpora, and we also examine the necessary conditions for its activation, as well as restrictions and contextual clues which enable its identification. The analyses are carried out in order to observe, discover and draw conclusions about the reifying potential and reifying peculiarities of the Italian demonstrative variable pronoun "questo".